2006
DOI: 10.1007/s00417-006-0386-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of matrix metalloproteinases in the subretinal fluid correlates with the extent of rhegmatogenous retinal detachment

Abstract: MMPs and TIMP-1 levels are elevated in SRF during RRD. A regression model consisting of MMP-3, MMP-8 and proMMP-9 may be proved to be of potential use in providing information for evaluation of the extent of RRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 25 publications
1
15
0
1
Order By: Relevance
“…A previous study using an animal retinal detachment model showed that subretinal fluid interferes with normal diffusion of oxygen and nutrients from the retinal pigment epithelium to photoreceptors and thus could induce photoreceptor degeneration [12]. Moreover, the high concentration of degradative enzymes in the subretinal fluid might have resulted in something more than simple diffusion-blockage in rhegmatogenous retinal detachment [14,15]. Second, in the three cases, there might have been additional defects in structural factors in the subretinal space which could not be detected with SD-OCT, i.e., connections between photoreceptor and retinal pigment epithelium or interphotoreceptor matrix [16].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study using an animal retinal detachment model showed that subretinal fluid interferes with normal diffusion of oxygen and nutrients from the retinal pigment epithelium to photoreceptors and thus could induce photoreceptor degeneration [12]. Moreover, the high concentration of degradative enzymes in the subretinal fluid might have resulted in something more than simple diffusion-blockage in rhegmatogenous retinal detachment [14,15]. Second, in the three cases, there might have been additional defects in structural factors in the subretinal space which could not be detected with SD-OCT, i.e., connections between photoreceptor and retinal pigment epithelium or interphotoreceptor matrix [16].…”
Section: Discussionmentioning
confidence: 99%
“…MMP gelatinolytic activity was determined by gelatin zymography analysis using sodium dodecyl sulphate–polyacrylamide gel electrophoresis (SDS–PAGE) under denaturing but non‐reducing conditions, as described previously (Karakiulakis et al. 1997; Symeonidis et al. 2007b).…”
Section: Methodsmentioning
confidence: 99%
“…We have shown previously that a regression model consisting of MMP‐3, MMP‐8 and proMMP‐9 may be of use in providing new information for the evaluation of RRD extent (Symeonidis et al. 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…epiretinal membranes). 14 RRD appears to be an environment of stimuli for the production of a variety of factors with far-ranging activities and functions. In a study by LaHeij et al, basic fibroblast growth factor (BFGF), glutamine synthetase, and interleukin (IL)-6 were found to be elevated in the SRF during RRD.…”
Section: Rpe Cells Have Been Shown To Be Constituents Of the Srf In Rmentioning
confidence: 99%